(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The objective of this study is to examine the perceptions of healthcare professionals in several healthcare settings on the roles and duties of nurses in promoting community health. However, there were differences in responses on the involvement of community members in decision-making processes, addressing the socioeconomic factors that influence health, facing obstacles in engaging communities, and receiving recognition for their efforts. The findings suggest that healthcare professionals recognize the importance of nurses in promoting healthy behaviors and improving health outcomes in communities. An explicit consensus was seen in significant domains, such as collaboration, practices grounded on empirical data, empowerment, and support from the organization, highlighting the pivotal role of nurses in initiatives aimed at promoting community health. The study identified inconsistencies in views, indicating the need for more examination and potential opportunities to improve nurses’ involvement in health promotion. The results are important for healthcare organizations and policymakers in terms of supporting and improving the involvement of nurses in community health promotion. Healthcare professionals and organizations may work together to improve the efficacy of nurses in promoting healthy behaviors and preventing sickness by recognizing and addressing the various attitudes and barriers identified in this study.